Performance Analysis of Air Preheater to Improve the Efficiency in 210 MW Thermal Power Station - Selvamuthukumarasamy, R.; Manavalan, S. (International Journal of Psychosocial Rehabilitation, 2019)
The efficiency of the boiler in a 210 MW thermal power station is greatly dependent on the utilization of waste heat in the flue gas by the air preheater and economizer. The increase in efficiency of a 210 MW boiler can be achieved by increasing the performance of the air preheater and economizer. To reduce the leakages in the 210 MW air preheater and enhance heat transfer rate by changing the profile of the air preheater heating element surface will lead to an increase in the performance of the air preheater and economizer. In 210 MW north Chennai thermal power station/stage-I, a notched flat profile and single seal with 12 sector air pre heaters are used as heat transfer. These are replaced by double undulated profile heating elements and double seals with 24 sectors in air preheaters. Hence heat loss in the air preheater is minimized, and the air preheater absorbs additional heat from exhaust flue gas. The profile change in heating element and double-sealed arrangement air preheater are to be analyzed. Based on the results, the percentages of efficiency in the air preheater are to be calculated.